Lignin-derived nitrogen-doped solid acid as well as preparation method and application thereof

By mixing lignin with nitrogen-containing reagent and sulfonating it, an efficient nitrogen-doped solid acid catalyst was prepared, which solved the problems of poor stability of carbon-based solid acids in hydrothermal environments and low yield of furfural in a hydrothermal environment, and achieved efficient catalytic performance With green and environmentally friendly solid acid catalyst, the yield rate of furfural reaches 94%.

CN119140138APending Publication Date: 2024-12-17HUATAI GROUP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411062370.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, the carbon-based solid acid-derived catalyst has poor stability in a hydrothermal environment and low yield on furfural preparation in a directionally induced xylose.

Method used

By mixing lignin with nitrogen-containing reagents, nitrogen-doped carbon sphere materials are prepared and sulfonated by sulfonation reagents, an efficient and stable solid acid catalyst is obtained for catalyzing the conversion of xylose to furfural. The method includes reacting lignin with a nitrogen-containing reagent at a certain temperature to form a nitrogen-doped carbon sphere carrier, and then reacting with a sulfonation reagent to form a highly effective solid acid.

Benefits of technology

It improves the stability and reaction efficiency of the catalyst, has excellent catalytic performance, and the yield of furfural can reach up to 94%. It uses waste lignin as raw material, which is in line with the concept of green development, and the preparation method is simple and easy to use on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140138A_ABST
    Figure CN119140138A_ABST
Patent Text Reader

Abstract

The invention discloses lignin-derived nitrogen-doped solid acid as well as a preparation method and application thereof, and relates to the technical field of solid acid preparation. Comprising the following steps: S1, uniformly mixing lignin and derivative salts thereof with a nitrogen-containing reagent according to a certain proportion, transferring the mixture into a reaction kettle, preserving heat for a period of time at a certain temperature, cooling, washing and drying to obtain a lignin nitrogen-doped carbon sphere material; s2, transferring the obtained lignin nitrogen-doped microspheres into a tubular furnace, keeping the lignin nitrogen-doped microspheres at a certain temperature for a period of time in a nitrogen atmosphere, and washing and drying after carbonization is completed to obtain a lignin nitrogen-doped carbon sphere carrier; s3, transferring the obtained lignin nitrogen-doped carbon sphere carrier and a sulfonating reagent into a three-neck flask according to a certain solid-to-liquid ratio, reacting for a certain time, and washing and drying to obtain the lignin nitrogen-doped solid acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a lignin-derived nitrogen-doped solid acid and a preparation method and application thereof, and relates to the technical field of solid acid preparation. Background Art

[0002] The furan ring and aldehyde structure in the furfural structure make it chemically active. It can not only be used directly, but also be further converted into a series of compounds as an intermediate, and can also be used to make liquid fuels and fuel additives. As an important monomer, furfural can undergo a variety of chemical reactions and is used to produce furan derivatives, such as furfuryl alcohol, methyl furan, furoic acid, succinic acid, etc., as a selective solvent for separating unsaturated aliphatic compounds, as a decolorant for rosin, and as a raw material for furan resins. It plays an important role in modern chemical industry and is currently the only important chemical raw material that is completely dependent on biomass refining.

[0003] At present, furfural is mainly produced in industry through homogeneous acid hydrolysis, which has the characteristics of high catalytic efficiency and good reaction effect. However, due to the use of liquid acid, the catalyst cannot be recovered and the equipment is seriously corroded. Summary of the invention

[0004] In view of the problems of the prior art, the present invention provides a lignin-derived nitrogen-doped solid acid and a preparation method and application thereof, which overcome the shortcomings of poor stability of carbon-based solid acid-derived catalysts in a hydrothermal environment and low yield of furfural prepared by directional induction of xylose.

[0005] The specific scheme proposed by the present invention is:

[0006] The present invention provides a method for preparing a lignin-derived nitrogen-doped solid acid, comprising the following steps:

[0007] S1: After lignin and its derivative salts and nitrogen-containing reagents are mixed uniformly in a certain proportion, they are transferred to a reactor, kept at a certain temperature for a period of time, cooled, washed and dried to obtain lignin nitrogen-doped carbon ball materials;

[0008] S2: The obtained lignin nitrogen-doped microspheres are transferred to a tube furnace in a nitrogen atmosphere and kept at a certain temperature for a period of time. After carbonization, the microspheres are washed and dried to obtain lignin nitrogen-doped carbon sphere carriers;

[0009] S3: The obtained lignin nitrogen-doped carbon ball carrier and the sulfonation reagent are transferred to a three-necked flask according to a certain solid-liquid ratio, and after a certain reaction time, the lignin nitrogen-doped solid acid is obtained by washing and drying.

[0010] Furthermore, the lignin and its derived salts described in S1 of the method for preparing a lignin-derived nitrogen-doped solid acid include one or more combinations of sodium lignin sulfonate, calcium lignin sulfonate, enzymatic lignin, acid-precipitated lignin, and organic solvent lignin;

[0011] The nitrogen-containing reagent in S1 is one or more combinations of urea, melamine, ammonium carbonate, ammonium sulfate, and amino acids.

[0012] Furthermore, in the method for preparing a lignin-derived nitrogen-doped solid acid, the mass ratio of the lignin and its derivative salt to the nitrogen-containing reagent in S1 is 1:3-3:1, and the solid-liquid ratio of the added water to the solid is 1:50-1:200 g / mL.

[0013] Furthermore, in S1 of the method for preparing a lignin-derived nitrogen-doped solid acid, the reaction temperature in the reactor is 180° C.-240° C., and the reaction time is 6-18 hours.

[0014] Furthermore, in the method for preparing a lignin-derived nitrogen-doped solid acid, the carbonization temperature in S2 is 400° C.-800° C., and the insulation time is 1-3 hours.

[0015] Furthermore, the sulfonating agent described in S3 of the method for preparing a lignin-derived nitrogen-doped solid acid is one or more of concentrated sulfuric acid, perchloric acid, potassium permanganate, hydrogen peroxide, and hypochlorous acid.

[0016] Furthermore, in S3 of the method for preparing a lignin-derived nitrogen-doped solid acid, the solid-liquid ratio of the lignin nitrogen-doped carbon ball carrier to the sulfonated reagent is 1:5-1:50 g / mL, the reaction temperature is 100°C-210°C, and the reaction time is 1-4 h.

[0017] The present invention also provides a lignin-derived nitrogen-doped solid acid, which is prepared according to the preparation method of the lignin-derived nitrogen-doped solid acid.

[0018] The present invention also provides an application of a nitrogen-doped solid acid derived from lignin, wherein the nitrogen-doped solid acid derived from lignin is used as a catalyst in catalyzing xylose to prepare furfural.

[0019] Furthermore, in the application of the nitrogen-doped solid acid derived from lignin, when the nitrogen-doped solid acid derived from lignin is used as a catalyst in the reaction of catalyzing hemicellulose to prepare furfural, the method comprises the following steps:

[0020] Xylose and lignin-derived nitrogen-doped solid acid catalysts are added into a hydrothermal reactor in a mass ratio of 1:1-5:1 and an organic solvent is added, and the reaction is carried out at 130° C.-200° C. for 60-180 minutes to obtain furfural.

[0021] The benefits of the present invention are:

[0022] The method of the present invention utilizes lignin and a nitrogen-containing reagent to simultaneously prepare a carbon material containing nitrogen and a spherical shape under hydrothermal conditions. On the one hand, the introduction of nitrogen improves the electronegativity of the material, which is beneficial to the subsequent surface modification and functionalization; on the other hand, the method of the present invention obtains a lignin nitrogen-doped carbon ball structure through hydrothermal treatment, which increases the probability of active sites in contact with the substrate and greatly improves the reaction efficiency. Moreover, the obtained spherical carbon material is subjected to secondary carbonization, which improves the degree of graphitization of the carbon material and greatly improves the subsequent sulfonation and modification. Finally, a sulfonating agent is used to sulfonate the nitrogen-doped carbon ball carrier to obtain an efficient and stable solid acid catalyst. In addition, the catalyst uses waste lignin as a raw material, which is in line with the concept of green development, and the preparation method is simple and easy to prepare and use on a large scale.

[0023] The lignin-derived nitrogen-doped solid acid catalyst prepared by the present invention has high surface acid content, is not easy to lose active sites, and has good catalytic performance.

[0024] The present invention also discloses the nitrogen-doped solid acid derived from lignin as a catalyst for preparing furfural from xylose. According to experiments, the total acidity of the solid acid of the present invention can reach 1.68-1.87 mmol / g, and the furfural yield can reach up to 94%, which has an excellent catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the SEM picture of the solid acid catalyst of the present invention.

[0026] Figure 2 This is a graph of ammonia adsorption of the solid acid catalyst of the present invention. In the graph, the red color represents solid acid not doped with nitrogen, and the blue color represents solid acid doped with nitrogen. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0028] Example 1

[0029] The present invention provides a method for preparing a lignin-derived nitrogen-doped solid acid, comprising the following steps:

[0030] S1: Take 2.0g sodium lignin sulfonate and 1.0g urea and dissolve them in 150mL deionized water. Transfer the solution to a 200mL reactor and react at 230℃ for 12 hours. After the reaction is completed, wash it with deionized water and ethanol alternately for several times and dry it at 80℃ for 12 hours to obtain lignin-derived nitrogen-doped carbon microspheres.

[0031] S2: The carbon microsphere material obtained above was placed in a tube furnace and pyrolyzed at 600° C. for 2 hours in a nitrogen atmosphere. The obtained sample was washed with hydrochloric acid and a large amount of deionized water, and then dried at 105° C. to obtain a lignin-derived nitrogen-doped carbon microsphere carrier.

[0032] S3: The lignin-derived nitrogen-doped carbon microsphere carrier was mixed with concentrated sulfuric acid in a ratio of 1:30 (g / mL), reacted at 150°C for 10 hours, washed with a large amount of deionized water until neutral, and dried in an oven at 80°C. The obtained product was the lignin-derived nitrogen-doped solid acid.

[0033] The present invention obtains nitrogen-doped solid acid derived from lignin. After measurement, the acid value of the sample is 1.87 mmol / g. Figure 1 The morphology of the prepared solid acid catalyst shows that the solid acid catalyst has a spherical structure, which will increase the contact area between the catalyst and the substrate and effectively improve the catalytic efficiency.

[0034] In the application of the present invention, the prepared lignin-derived nitrogen-doped solid acid is used for xylose conversion to prepare furfural: 0.10 g of xylose, 0.05 g of lignin-derived nitrogen-doped solid acid, 5 mL of dichloromethane and 5 mL of deionized water are added to a 150 mL pressure-resistant reaction tube, and the reaction temperature is 180° C. and maintained for 120 minutes under magnetic stirring, and the yield of furfural obtained is 94%.

[0035] Example 2

[0036] The method of the present invention comprises:

[0037] S1: Take 2.0g of calcium lignin sulfonate and 1.0g of ammonium sulfate and dissolve them in 150mL of deionized water. Transfer the solution to a 200mL reactor and react at 240°C for 12 hours. After the reaction is completed, wash it with deionized water and ethanol alternately for several times and dry it at 80°C for 12 hours to obtain lignin-derived nitrogen-doped carbon microspheres.

[0038] S2: The carbon microsphere material obtained above was placed in a tube furnace and pyrolyzed at 600° C. for 2 hours in a nitrogen atmosphere. The obtained sample was washed with hydrochloric acid and a large amount of deionized water, and then dried at 105° C. to obtain a lignin-derived nitrogen-doped carbon microsphere carrier.

[0039] S3: The lignin-derived nitrogen-doped carbon microsphere carrier was mixed with concentrated sulfuric acid in a ratio of 1:30 (g / mL), reacted at 150°C for 10 hours, washed with a large amount of deionized water until neutral, and dried in an oven at 80°C. The obtained product was the lignin-derived nitrogen-doped solid acid.

[0040] According to the measurement, the acid value of the nitrogen-doped solid acid obtained in the present invention is 1.68 mmol / g.

[0041] When the prepared lignin-derived nitrogen-doped solid acid is used in the application of xylose conversion to prepare furfural, 0.10g xylose, 0.05g lignin-derived nitrogen-doped solid acid, 5mL dichloromethane and 5mL deionized water are added to a 150mL pressure-resistant reaction tube. Under magnetic stirring, the reaction temperature is 180°C and maintained for 120min. The furfural yield obtained is 89.5%.

[0042] Example 3

[0043] The method of the present invention comprises:

[0044] S1: Take 2.0g sodium lignin sulfonate and 1.0g urea and dissolve them in 150mL deionized water. Transfer the solution to a 200mL reactor and react at 200°C for 12 hours. After the reaction is completed, wash it with deionized water and ethanol alternately for several times and dry it at 80°C for 12 hours to obtain lignin-derived nitrogen-doped carbon microspheres.

[0045] S2: The carbon microsphere material obtained above was placed in a tube furnace and pyrolyzed at 600° C. for 2 hours in a nitrogen atmosphere. The obtained sample was washed with hydrochloric acid and a large amount of deionized water, and then dried at 105° C. to obtain a lignin-derived nitrogen-doped carbon microsphere carrier.

[0046] S3: The lignin-derived nitrogen-doped carbon microsphere carrier was mixed with concentrated sulfuric acid in a ratio of 1:30 (g / mL), reacted at 150°C for 10 hours, washed with a large amount of deionized water until neutral, and dried in an oven at 80°C. The obtained product was the lignin-derived nitrogen-doped solid acid.

[0047] According to the measurement, the acid value of the nitrogen-doped solid acid obtained in the present invention is 1.79 mmol / g.

[0048] When the prepared lignin-derived nitrogen-doped solid acid is used in the application of xylose conversion to prepare furfural, 0.10g xylose, 0.05g lignin-derived nitrogen-doped solid acid, 5mL dichloromethane and 5mL deionized water are added to a 150mL pressure-resistant reaction tube. Under magnetic stirring, the reaction temperature is 180°C and maintained for 120min. The furfural yield obtained is 92%.

[0049] from Figure 2It can be seen that the acidity of the solid acid catalyst not doped with nitrogen shows a decreasing trend, which is related to the fact that nitrogen doping changes the electronic configuration of the carbon material. It also proves that the doping of nitrogen in the method of the present invention improves the acidity and catalytic effect of the catalyst.

[0050] Example 4

[0051] The method of the present invention comprises:

[0052] S1: Take 2.0g sodium lignin sulfonate and 1.0g urea and dissolve them in 150mL deionized water. Transfer the solution to a 200mL reactor and react at 230℃ for 12 hours. After the reaction is completed, wash it with deionized water and ethanol alternately for several times and dry it at 80℃ for 12 hours to obtain lignin-derived nitrogen-doped carbon microspheres.

[0053] S2: The carbon microsphere material obtained above was placed in a tube furnace and pyrolyzed at 500° C. for 2 hours in a nitrogen atmosphere. The obtained sample was washed with hydrochloric acid and a large amount of deionized water, and then dried at 105° C. to obtain a lignin-derived nitrogen-doped carbon microsphere carrier.

[0054] S3: The lignin-derived nitrogen-doped carbon microsphere carrier is mixed with concentrated sulfuric acid in a ratio of 1:30 (g / mL), reacted at 150°C for 10 hours, washed with a large amount of deionized water until neutral, and dried in an oven at 80°C. The obtained product is the lignin-derived nitrogen-doped solid acid.

[0055] According to the measurement, the acid value of the nitrogen-doped solid acid obtained in the present invention is 1.73 mmol / g.

[0056] When the prepared lignin-derived nitrogen-doped solid acid is used in the application of xylose conversion to prepare furfural, 0.10g xylose, 0.05g lignin-derived nitrogen-doped solid acid, 5mL dichloromethane and 5mL deionized water are added to a 150mL pressure-resistant reaction tube. Under magnetic stirring, the reaction temperature is 180°C and maintained for 120min. The furfural yield obtained is 90.3%.

[0057] It can be seen from Examples 3 and 4 that, within the technical solution of the method of the present invention, increasing the carbonization temperature is more conducive to increasing the acidity and furfural yield of the obtained carbon material. It also indirectly proves that the secondary carbonization of the spherical carbon material obtained in the method of the present invention improves the degree of graphitization of the carbon material. High graphitization is beneficial to improving the sulfonation effect of the carbon material, thereby enhancing the conversion of xylose into furfural.

[0058] Based on the technical scheme of the preparation method of the present invention, according to the actual situation, specific reagents or reagent combinations among lignin and its derivative salts, nitrogen-containing reagents, and sulfonated reagents can be selected, and the amounts thereof can be adjusted to obtain effects similar to those of Example 1. The total acidity of the solid acid is mainly in the range of 1.68-1.87 mmol / g, and the yield of furfural is mainly in the range of 89.5%-94%.

[0059] The lignin used in the present invention is one of the most abundant and renewable biomass in the world, and is a waste byproduct or low-value product of biomass refineries, especially papermaking enterprises. It contains abundant benzene ring structures and is easily graphitized during pyrolysis, which is beneficial to its subsequent modification, sulfonation or functionalization, thereby obtaining an efficient and stable solid acid catalyst.

[0060] Other reagents used in the present invention are all reagents that can be purchased or prepared in the prior art and will not be described again.

[0061] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing a lignin-derived nitrogen-doped solid acid, characterized in that The following steps are involved: S1: After lignin and its derivative salts and nitrogen-containing reagents are mixed uniformly in a certain proportion, they are transferred to a reactor, kept at a certain temperature for a period of time, cooled, washed and dried to obtain lignin nitrogen-doped carbon ball materials; S2: The obtained lignin nitrogen-doped microspheres are transferred to a tube furnace in a nitrogen atmosphere and kept at a certain temperature for a period of time. After carbonization, the microspheres are washed and dried to obtain lignin nitrogen-doped carbon sphere carriers; S3: The obtained lignin nitrogen-doped carbon ball carrier and the sulfonation reagent are transferred to a three-necked flask according to a certain solid-liquid ratio, and after a certain reaction time, the lignin nitrogen-doped solid acid is obtained by washing and drying.

2. The method for preparing a lignin-derived nitrogen-doped solid acid according to claim 1, wherein the lignin and its derived salts described in S1 include one or more combinations of sodium lignin sulfonate, calcium lignin sulfonate, enzymatic lignin, acid-precipitated lignin, and organic solvent lignin; The nitrogen-containing reagent in S1 is one or more combinations of urea, melamine, ammonium carbonate, ammonium sulfate, and amino acids.

3. The method for preparing a lignin-derived nitrogen-doped solid acid according to claim 1, characterized in that the mass ratio of the lignin and its derivative salt described in S1 to the nitrogen-containing reagent is 1:3-3:1, and the solid-liquid ratio of the added water to the solid is 1:50-1:200 g / mL.

4. The method for preparing a lignin-derived nitrogen-doped solid acid according to claim 1, characterized in that The reaction temperature in the reactor in S1 is 180°C-240°C, and the reaction time is 6-18h.

5. The method for preparing a lignin-derived nitrogen-doped solid acid according to claim 4, characterized in that the carbonization temperature in S2 is 400°C-800°C and the insulation time is 1-3h.

6. The method for preparing a lignin-derived nitrogen-doped solid acid according to claim 1, wherein the sulfonating agent in S3 is one or more of concentrated sulfuric acid, perchloric acid, potassium permanganate, hydrogen peroxide, and hypochlorous acid.

7. The method for preparing a lignin-derived nitrogen-doped solid acid according to claim 1, characterized in that the solid-liquid ratio of the lignin nitrogen-doped carbon ball carrier to the sulfonated reagent in S3 is 1:5-1:50 g / mL, the reaction temperature is 100° C.-210° C., and the reaction time is 1-4 h.

8. A lignin-derived nitrogen-doped solid acid, characterized in that The method for preparing a lignin-derived nitrogen-doped solid acid according to any one of claims 1 to 7.

9. An application of a lignin-derived nitrogen-doped solid acid, characterized in that The lignin-derived nitrogen-doped solid acid is used as a catalyst in catalyzing xylose to prepare furfural.

10. The use of a lignin-derived nitrogen-doped solid acid according to claim 9, characterized in that When the nitrogen-doped solid acid derived from lignin is used as a catalyst in the reaction of catalyzing hemicellulose to prepare furfural, the method comprises the following steps: Xylose and lignin-derived nitrogen-doped solid acid catalysts are added into a hydrothermal reactor in a mass ratio of 1:1-5:1 and an organic solvent is added, and the reaction is carried out at 130° C.-200° C. for 60-180 minutes to obtain furfural.

Citation Information

Patent Citations

  • Preparation method of rice husk carbon-based solid acid catalyst and surface acid concentration testing method

    CN106732674A

  • Preparation method of nitrogen-doped carbon microsphere supported platinum composite catalyst for DMFC (direct methanol fuel cell)

    CN108448130A

  • Black liquor-based solid acid catalyst, preparation method thereof and application of black liquor-based solid acid catalyst in furfural production

    CN115430439A

  • Method for decomposition of basic substance by photocatalyst and photocatalyst used for the decomposition

    JP2004105904A